Definitions of Government in IMF-Supported Programs - Dziobek, Claudia (Technical Notes and Manuals; Technical Notes and Manuals ;, 2013)
This note addresses the following main issues: -- Statistical definitions of government (Government Finance Statistics Manual 2001) -- Institutional structure of government and public sector -- What is a precise definition of government and why it is relevant -- Potential pitfalls of lacking a precise definition of government -- Definitions of government in IMF-supported programs -- Applications for fiscal rules and other fiscal policy design.